7^x :49=7^27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
7^x : 49 =7^27
=> 7^x = 7^27 . 7^2
=> 7^x = 7^29
=> x = 29
Vậy x = 29
\(7^x\cdot49=7^{27}\)
\(7^x\cdot7^2=7^{27}\)
\(7^x=7^{27}:7^2\)
\(7^x=7^{25}\)
\(x=25\)
Ta có -49/63=-21/27
Mà y/27=-21/27 suy ra y=-21
Lại có -21/27=-7/9
Mà 7/x=-7/9 suy ra x=-9
Vậy x=-9;y=-21
\(\frac{7}{x}=\frac{y}{27}=\frac{-49}{63}\)
Ta có:
\(\frac{7}{x}=\frac{-49}{63}\)
\(\Rightarrow-49.x=7.63\)
\(\Rightarrow-49x=441\)
\(\Rightarrow x=441:\left(-49\right)\)
\(\Rightarrow x=-9\)
\(\frac{y}{27}=\frac{-49}{63}\)
\(\Rightarrow y.63=-49.27\)
\(\Rightarrow63y=-1323\)
\(\Rightarrow y=\left(-1323\right):63\)
\(\Rightarrow y=-21\)
Vậy x = -9 ; y = -21
7x . 49 = 727
7x . 72 = 727
7x = 727 : 72
7x = 725
x = 25
Vậy x = 25
a: \(27^{2-x}< =9\)
=>\(\left(3^3\right)^{2-x}< =3^2\)
=>\(3^{6-3x}< =3^2\)
=>6-3x<=2
=>-3x<=-4
=>\(x>=\dfrac{4}{3}\)
b: \(7^{3-x}< 49\)
=>\(7^{3-x}< 7^2\)
=>3-x<2
=>-x<2-3=-1
=>x>1
c: \(27^{3-x}>9\)
=>\(\left(3^3\right)^{3-x}>3^2\)
=>\(3^{9-3x}>3^2\)
=>9-3x>2
=>-3x>-7
=>\(x< \dfrac{7}{3}\)
d: \(2^{3-x}< 2^3\)
=>3-x<3
=>-x<0
=>x>0
e: \(27^{3-x^2}< 27^{x+1}\)
=>\(3-x^2< x+1\)
=>\(-x^2-x+2< 0\)
=>\(x^2+x-2>0\)
=>(x+2)(x-1)>0
=>\(\left[{}\begin{matrix}x>1\\x< -2\end{matrix}\right.\)
5 + ( x + 27 ) = 64
( x + 27 ) = 64 - 5 ( x + 27 ) = 59 x = 59 - 27 x = 32a) \(\Rightarrow x+27=59\Rightarrow x=32\)
b) \(\Rightarrow x-2=39\Rightarrow x=41\)
c) \(\Rightarrow x+5=-322\Rightarrow x=-327\)
d) \(\Rightarrow5x=35\Rightarrow x=7\)
e) \(\Rightarrow4\left(x-5\right)=56\Rightarrow x-5=14\Rightarrow x=19\)
f) \(\Rightarrow15+x=37\Rightarrow x=22\)
g) \(\Rightarrow7\left(13-x\right)=35\Rightarrow13-x=5\Rightarrow x=8\)
h) \(\Rightarrow10\left(x+1\right)=100\Rightarrow x+1=10\Rightarrow x=9\)
a: \(x-\dfrac{10}{3}=\dfrac{7}{15}\cdot\dfrac{3}{5}\)
=>\(x-\dfrac{10}{3}=\dfrac{21}{75}=\dfrac{7}{25}\)
=>\(x=\dfrac{7}{25}+\dfrac{10}{3}=\dfrac{21+250}{75}=\dfrac{271}{75}\)
b: \(x+\dfrac{3}{22}=\dfrac{27}{121}\cdot\dfrac{9}{11}\)
=>\(x+\dfrac{3}{22}=\dfrac{243}{1331}\)
=>\(x=\dfrac{243}{1331}-\dfrac{3}{22}=\dfrac{123}{2662}\)
c: \(\dfrac{8}{23}\cdot\dfrac{46}{24}-x=\dfrac{1}{3}\)
=>\(\dfrac{8}{24}\cdot\dfrac{46}{23}-x=\dfrac{1}{3}\)
=>\(\dfrac{2}{3}-x=\dfrac{1}{3}\)
=>\(x=\dfrac{2}{3}-\dfrac{1}{3}=\dfrac{1}{3}\)
d: \(1-x=\dfrac{49}{65}\cdot\dfrac{5}{7}\)
=>\(1-x=\dfrac{49}{7}\cdot\dfrac{5}{65}=\dfrac{7}{13}\)
=>\(x=1-\dfrac{7}{13}=\dfrac{6}{13}\)
a) 3x - 21 = 27
3x = 27 + 21
3x= 48
x = 48 : 3
x= 16
b) -7 - x + 14 = 49
-7 - x = 49 - 14
-7 - x = 35
x = 35 : (-7)
x = -5
\(7^x:49=7^{27}\)
\(7^x:7^2=7^{27}\)
\(7^x\) \(=7^{27}.7^2=7^{29}\)
Vậy x = 29
K mk mk đầu tiên nhá
\(7^x:49=7^{27}\)
\(\Rightarrow7^x:49=49^{26}\)
\(\Rightarrow7^x=49^{26}:49=49^{25}\)
\(\Rightarrow x=25\)
tíc mình nha